Intraocular Dexamethasone Implant as Adjunct to Silicone Oil Tamponade for Proliferative Vitreoretinopathy - Sherif, M.; Wolfensberger, T. J. (Klinische Monatsblätter für Augenheilkunde, 2017)
Background Proliferative vitreoretinopathy (PVR) occurs in 10 % of patients with retinal detachment and is characterized by excessive epi-, sub- or intraretinal contraction. Corticosteroids have been shown to counter this contraction. Patients and Methods Retrospective review of 5 patients (3 females, 2 males) with recurrent retinal detachment with stage C PVR. The mean age was 61.2 ± 20.5 years and myopia > − 5.0 dioptres was present in 3 eyes. Patients were treated with 23 g vitrectomy, retinectomy and endolaser, dexamethasone (Ozurdex®) injection under perfluorocarbone and 5500 cs silicone oil tamponade. Results After a total follow-up of 8.8 ± 6.4 months with silicone oil tamponade, the Ozurdex® implant was localised in the macula in 1 case, and in 4 cases behind the iris with a completely attached retina. Preoperative intraocular pressure was 11.0 ± 4.0 mmHg, which remained stable at 7.8 ± 3.5 mmHg at the end of the final follow-up. No localised adverse effects were observed of the implant on the retina or the iris. Conclusions The dexamethasone implant Ozurdex® is well tolerated in conjunction with silicone oil tamponade in eyes with retinal detachment and PVR. The implant may be a potential candidate for the prevention of PVR.
Keywords: Proliferative vitreoretinopathy; vitrectomy; silicone oil; dexamethasone; Ozurdex